Tata Kelola Kolaboratif dalam Intervensi Stunting di Kabupaten Tuban - Denny Iswanto; Ria Fitriani (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
Tuban Regency has succeeded in reducing stunting rates in the last seven years, but the percentage of stunting in Tuban Regency still exceeds the national rate and East Java Province. This is due to the lack of collaboration between various sectors in dealing with stunting problems in Tuban Regency. This study emphasizes the importance of cross-sectoral collaboration in handling stunting problems in Tuban Regency, which is analyzed using a collaborative governance perspective. This research uses qualitative data from previous research and credible and relevant institutional administrative data related to stunting in Tuban Regency. The phenomenon studied is described as a description that shows the need for collaboration between stakeholders and focuses on mapping collaborative governance to reduce the prevalence of stunting in Tuban Regency. Collaborative governance in accelerating efforts to tackle stunting in Tuban Regency still needs to be improved, which is marked by the uneven formation of the Team for the Acceleration of Stunting Handling (TPPS). Only 17 out of 311 villages (5.5%) in Tuban Regency have established TPPS, so the stunting reduction rate in Tuban Regency is still far from the regional target of 17% and the national target of 14%. Villages with TPPS members must also fully understand their main duties and functions. Poverty and socio-cultural factors of the people of Tuban Regency also influence. Collaboration could be more optimal and community involvement needs to be active. The efforts to deal with stunting in Tuban Regency can be more effective and sustainable with better collaboration and adequate capacity building.